2021
DOI: 10.1080/1750984x.2021.1901298
|View full text |Cite
|
Sign up to set email alerts
|

The application of Goal Setting Theory to goal setting interventions in sport: a systematic review

Abstract: Goal setting is one of the most frequently used mental skills in sports, and Goal Setting Theory has been the most prominent theoretical framework upon which goal setting interventions are based. The present study provides a systematic review examining how the tenets of GST have been applied to goal setting interventions in sport. A total of 27 peer-reviewed studies written in English, which implemented goal setting interventions with athletes in a sport-specific, applied (i.e. non-laboratory) context, were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 57 publications
1
36
3
Order By: Relevance
“…If we consider these findings in comparison with our results and in the framework of the goal setting theory, we shall remember that the specificity and precision, with which we define a goal, are crucial for the quality of the performance, as well as for the allocation of attention and the necessary motivation [42,52]. Moreover, in their recent review, Jeong et al [15] reminded that Locke and Latham [11] suggested that goal specificity should be combined with goal difficulty for effective goal setting. Our third overarching theme, "Trying to hold on", reflects Ntoumanis and Sedikides [7] concept of 'goal persistence'.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…If we consider these findings in comparison with our results and in the framework of the goal setting theory, we shall remember that the specificity and precision, with which we define a goal, are crucial for the quality of the performance, as well as for the allocation of attention and the necessary motivation [42,52]. Moreover, in their recent review, Jeong et al [15] reminded that Locke and Latham [11] suggested that goal specificity should be combined with goal difficulty for effective goal setting. Our third overarching theme, "Trying to hold on", reflects Ntoumanis and Sedikides [7] concept of 'goal persistence'.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover it was found that self-avoidance goals (where the athletes try to avoid self-based incompetence) are not always maladaptive, and that, in the situation of confinement, it might be beneficial to shift among multiple goals. While informative, this study fails to answer Jeong et al's [15] call for future research to consider empirical approaches that are based on coaches' experiential knowledge and the recommendation to include qualitative approaches to identify practitioners', coaches', and athletes' perspectives on goal setting. In a similar fashion, to date research investigating the effects of the COVID-19 pandemic in sport mainly adopted a quantitative approach, with only few exceptions [20], despite a growing interest of -and need for -qualitative studies in the field of sport psychology [21].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations